Quantification of solute diffusivity in osteoarthritic human femoral cartilage using correlation spectroscopy. Issue 12 (25th September 2018) - Graham, Brian T.; Wright, Alison D.; Burris, David L.; Axe, Michael J.; Raisis, Leo W.; Price, Christopher
ABSTRACT: Osteoarthritis is a chronic joint disease characterized by articular cartilage degeneration, pain, and disability. As an avascular tissue, the movement of water and solutes through the tissue is critical to cartilage health and function, and early changes in solute diffusivity due to micro‐scale changes in the properties of cartilage's extracellular matrix might precede clinical symptoms. A diagnostic technique for quantifying alteration to the diffusive environment of cartilage that precedes macroscopic changes may allow for the earlier identification of osteoarthritic disease, facilitating earlier intervention strategies. Toward this end, we used two confocal microscopy‐based correlation spectroscopy techniques, fluorescence correlation spectroscopy and raster image correlation spectroscopy, to quantify the diffusion of two small solutes, fluorescein and 3k dextran, within human osteoarthritic articular cartilage. Our goal was to determine if these relatively simple optical correlation spectroscopy techniques could detect changes in solute diffusivity associated with increasing cartilage damage as assessed by International Cartilage Repair Society scoring guidelines, and if these measures are correlated with mechanical and compositional measures of cartilage health. Our data show a modest, yet significant increase in solute diffusivity and cartilage permeability with increasing osteoarthritis score (grades 0–2), with a strong correlation between diffusion coefficients, permeability, and cartilage composition. The described correlation spectroscopy techniques are quick, simple, and easily adapted to existing laboratory workflow and equipment. Furthermore, the minimal solute concentrations and laser powers required for analysis, combined with recent advances in arthroscopic microscopy, suggest correlation spectroscopy techniques as translational candidates for development into early OA diagnosis tools. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:3256–3267, 2018.